Differentially expressed microRNAs in biochemically characterized FrieswalTM crossbred bull semen. Issue 1 (1st February 2023) - Singh, Rani; Deb, Rajib; Sengar, Gyanendra Singh; Raja, T. V.; Kumar, Sushil; Singh, Umesh; Das, A. K.; Alex, Rani; Kumar, Amod; Tyagi, Shrikant; Pal, Prasanna; Patil, N. V.
Abstract: In addition to the transmission of paternal genome, spermatozoa also carry coding as well as noncoding microRNAs (miRNAs) into the female oocyte during the process of biological fertilization. Based on RNA deep sequencing, a total 28 number of differentially expressed miRNAs were cataloged in categorized Frieswal TM crossbred (Holstein Friesian X Sahiwal) bull semen on the basis of conception rate (CR) in field progeny testing program. Validation of selected miRNAs viz. bta-mir-182, bta-let-7b, bta-mir-34c and bta-mir-20a revealed that, superior bull semen having comparatively ( p < .05) lower level of all the miRNAs in contrast to inferior bull semen. Additionally, it was illustrated that, bta-mir-20a and bta-mir-34c miRNAs are negatively ( p < .01) correlated with seminal plasma catalase (CAT) activity and glutathione peroxidase (GPx) level. Interactome studies identified that bta-mir-140, bta-mir-342, bta-mir-1306 and bta-mir-217 can target few of the important solute carrier (SLC) proteins viz. SLC30A3, SLC39A9, SLC31A1 and SLC38A2, respectively. Interestingly, it was noticed that all the SLCs were significantly ( p < .05) expressed at higher level in superior quality bull semen and they are negatively correlated ( p < .01) with their corresponding miRNAs as mentioned. This study may reflect the role of miRNAs in regulating few of the candidate genes and thus may influence the bull semen quality traits.